Pengaruh Unit Simpan Pinjam Terhadap Peningkatan Kesejahteraan Ekonomi Masyarakat Desa - Eka Kusuma Ramadani; Dewi Oktayani (JPS (Jurnal Perbankan Syariah), 2020)
This research aims to analyze and provide empirical evidence regarding the effect of the Penebal Teguh Mandiri savings and loan unit on improving the economic welfare of the Penebal village community. The problem in this research is that many people still use savings and loan units towards consumptive use. The data analysis method used is a quantitative analysis using validity and reliability tests, simple linear regression analysis, classical assumption test and the coefficient of determination using SPSS. The population used is the Penebal Village community with the criteria being the people who make loans at the Penebal Teguh Mandiri office of Penebal Village. The sample used was 174 people from the Penebal Village community. The results of this research indicate that only 38% of the level of influence of the savings and loan unit on the level of the economic welfare of the Penebal village community.